2022
DOI: 10.48550/arxiv.2202.00895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray Coronal Properties of Swift/BAT-Selected Seyfert 1 Active Galactic Nuclei

Nikita Kamraj,
Murray Brightman,
Fiona A. Harrison
et al.

Abstract: The corona is an integral component of Active Galactic Nuclei (AGN) which produces the bulk of the X-ray emission above 1-2 keV. However, many of its physical properties and the mechanisms powering this emission remain a mystery. In particular, the temperature of the coronal plasma has been difficult to constrain for large samples of AGN, as constraints require high quality broadband Xray spectral coverage extending above 10 keV in order to measure the high energy cutoff, which provides constraints on the comb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…However, we find no significant correlation between λ edd and Γ, or between λ edd and E cut in our sample (see Fig. 7), consistent with the results of Molina et al (2019), Hinkle & Mushotzky (2021) and Kamraj et al (2022). This is likely because the uncertainties in the measurements of λ edd are large, or the E cut -Γ correlation we find is not driven by Ed-dington ratio.…”
Section: The Underlying Mechanismssupporting
confidence: 79%
See 3 more Smart Citations
“…However, we find no significant correlation between λ edd and Γ, or between λ edd and E cut in our sample (see Fig. 7), consistent with the results of Molina et al (2019), Hinkle & Mushotzky (2021) and Kamraj et al (2022). This is likely because the uncertainties in the measurements of λ edd are large, or the E cut -Γ correlation we find is not driven by Ed-dington ratio.…”
Section: The Underlying Mechanismssupporting
confidence: 79%
“…6 in Fabian et al 2017). On the other hand, both the directly measured and conservatively estimated T e (1/3 E cut here, while 1/2 in Fabian et al 2015) of a considerable fraction of sources lie beyond (to the right of) the slab pair line, consistent with Kamraj et al (2022), favoring the sphere or hemisphere geometry. Considering the E cut -Γ relation shown above, it is implied that the coronal geometry might be spectral slope dependent, i.e., flatter shape for harder spectra, and rounder for softer spectra.…”
Section: The Underlying Mechanismssupporting
confidence: 53%
See 2 more Smart Citations
“…One of the constraints to get good estimate of E 𝑐𝑢𝑡 on a large sample of AGN is the lack of high signal to noise ratio data at energies beyond 50 keV, where the cut-off in the spectrum is defined. Though more measurements are now available from instruments such as NuSTAR (Fabian et al 2015;Buisson et al 2018;Kamraj et al 2018;Tortosa et al 2018;Ricci et al 2018;Rani & Stalin 2018;Rani et al 2019;Kang et al 2020;Baloković et al 2020;Akylas & Georgantopoulos 2021;Hinkle & Mushotzky 2021;Kamraj et al 2022), it is important to increase such measurements on a larger number of sources, firstly to find good estimates of E 𝑐𝑢𝑡 and secondly to find better constraints on the correlation of E 𝑐𝑢𝑡 with other physical properties of the sources. Also, variation in the temperature of the corona is now known in few radio-quiet category of AGN (Zhang et al 2018;Barua et al 2020Barua et al , 2021aKang et al 2021;Wilkins et al 2022;Pal et al 2022), however, it is not clear if it is shown by all AGN.…”
Section: Introductionmentioning
confidence: 99%